Lumbar sagittal plane spinal curvature and junior-level cricket players - Hecimovich, M. D.; Stomski, N. J. (International Journal of Athletic Therapy & Training, 2016)
Lumbar lordosis may be a risk factor for injury in junior-level athletes involved in sport which requires excessive amounts of extension. The purpose of this study was to examine the relationship between lumbar lordosis in junior-level cricket players with and without previous low back injury. Results demonstrated a statistically significant difference in lumbar lordosis between the two groups (LBI = 42.53 ± 9.10°; no LBI = 30.33 ± 8.36°; p < .01), with previous lower back injury accounting for 32% variation in lumbar lordosis (p < .01). The results indicate lumbar lordosis may be an issue worth examining in those athletes who partake in sports which have high levels of extension; but, as there is no accepted definition to lumbar postures, it is difficult to accurately interpret measurement results.